Virtual Laboratory for Engineering Education: Review of Virtual Laboratory for Students Learning - Ibham Veza; Ahmed Sule; Nicky Rahmana Putra; Muhammad Idris; Ihwan Ghazali; Irianto Irianto; Ulka Chandini Pendit; Gipin Mosliano; Arasmatusy (Engineering Science Letter, 2022)
E-learning is currently a rapidly growing trend which attempts to provide an infrastructural configuration that integrates and encompass learning content, services and tools as a single solution which can generate and deliver educational contents and training effectively, efficiently and cost-effectively. In advanced technical education, laboratories are essential learning spaces. Providing laboratory facilities at universities with limited funds and technical know-how is difficult due to the high expenses of installation and upkeep. In order to tackle these obstacles, "virtual laboratories" have been established. Through remote access, virtual laboratories make it possible for users to conduct experiments similar to genuine systems. Consequently, resources of laboratories can be shared across a wide community of geographically dispersed customers while restricting operational expenses and initial set-up to one single institution. This article reviews the virtual laboratory for engineering education. Three distinct e-learning resource methods are discussed. The intrinsic objectives of animation are also explained. Lastly, the conclusion is provided along with recommendation for future studies.